MATHEMATICAL SIMULATION FOR ASSESSMENT OF THE SMALL BUSINESS EFFICIENCY: REGIONAL ASPECTS - Zamkovyy, Oleksandr (My University, 2016)
Mathematical simulation of economic systems and processes are considered. The description of macroeconomic models for assets formation, consumer behaviour, production activity of an enterprise, and market balance is given. The line balance model of diversified economic system is examined.
Keywords: mathematical simulation, market balance, neural network, parameters, algorithm